Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
[45/(2 * 4.7) - (4.4)] * 6 = 54
Step 1: PEMDAS (Parenthesis first)
2 × 4.7 = 9.4
Step 2: Still within the parenthesis: 9.4 - 4.4 = 5
Step 3: Finish within the parenthesis: 45 ÷ 5 = 9
Step 4: Last part of the equation: 9 × 6 = 54
Correct placement of brackets and parenthesis to make the statement true is:
[45/(2x4.7)-(4.4)]x6 = 54
Step 1: PEMDAS (Parenthesis first)
2 × 4.7 = 9.4
Step 2: Still within the parenthesis: 9.4 - 4.4 = 5
Step 3: Finish within the parenthesis: 45 ÷ 5 = 9
Step 4: Last part of the equation: 9 × 6 = 54
Correct placement of brackets and parenthesis to make the statement true is:
[45/(2x4.7)-(4.4)]x6 = 54
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.